Group Communication Patterns In Building Trust In Jametal Line Group - Dzahana Shofa; Kezia Arum Sary (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to determine communication patterns in building trust in the Jametal line group. Effective communication patterns are built by Jametal admins to create a trust for members to purchase merchandise based on the delivery of information that can be received well, information disclosure by admins, honesty, admin ability to maintain communication to the kindness of admins who always integrate consistently. This type of research is qualitative through the case study method. Data collection techniques are observation, interviews, and documentation. The results showed that 3 (three) communication patterns occurred in the Jametal group, namely one-way communication patterns, two-way communication patterns, and multi-directional communication patterns. But the most dominant communication pattern is the two-way communication pattern. The pattern of one-way communication occurs during greetings every time a new member enters or leaves the group. Two-way communication patterns occur during the buying process to giving testimonials and multi-way communication patterns of buying and selling between members and admins. In forming trust, there are 3 (three) indicators, namely ability, kindness, and integrity. Ability to maintain communication, fulfill market desires and be open to all information. Kindness to create trust is shown by always responding positively and patiently whenever anyone asks or experiences confusion and the integrity of Jametal admin, which is always giving the best consistently, creating a sense of security and comfort for group members regarding merchandise and when communicating to create and maintain the trust of group members.